Implementación de un Sistema de Información para la Gestión de Proyectos de Inversión Pública en la Municipalidad Distrital de Alto Biavo - Pérez Saboya, Julio Cesar (2015)
This thesis, "IMPLEMENTATION OF AN INFORMATION SYSTEM FOR MANAGING PUBLIC INVESTMENT PROJECTS IN THE DISTRICT MUNICIPALITY OF ALTO BIAVO"; had as General Purpose, improve the management of public investment projects of the District Municipality of Alto Biavo. He also had specific objectives; Analyze information concerning the Management of Investment Projects, Project Management Automate Public Investment to determine the incidence of the computer system in the management of public investment projects For the development of the proposed different methodologies were used. For information gathering techniques were interviewed, as well as review and assessment documents; for the analysis and design object-oriented methodology (UML), the Unified Process and prototyping the PHP programming language used by the transmission PostgreSQL database and XAMMP Server package was used; each of these tools were used in order to meet the expectations of the municipality and minimize costs as they are software's free. View the reality of the mismanagement of public investment projects of the District Municipality of Alto Biavo, this research study assessed the extent the management of public investment projects with the implementation of a computer system is improved